Resource Management in Public Sensing - Challenges and Requirements - Herrmann, Klaus; Fischer, Daniel (Electronic Communications of the EASST, 2011)
Public sensing is a new research area emerging from the fields of wireless sensor networks and mobile computing. The idea of public sensing is to use the huge number of heterogenous, uncontrollable sensors and system resources which are readily available in the mobile phones of users and in the environment to execute sensing tasks. For example, such sensors can be used to find the shortest route in a traffic navigation application. In order to plan, execute and adapt sensing tasks, applications need to be able to query for the available resources, e.g. ensity of certain sensors, in a given area. In this work, we investigate the challenges of providing such information and deduce requirements for a resource management system in public sensing. In addition, we propose and discuss concepts that cope with those challenges.